Safety Priorities and Underestimations in Recreational Scuba Diving Operations: A European Study Supporting the Implementation of New Risk Management Programmes - Lucrezi, Serena; Egi, Salih Murat; Pieri, Massimo; Burman, Francois; Ozyigit, Tamer; Cialoni, Danilo; Thomas, Guy; Marroni, Alessandro; Saayman, Melville (Frontiers in Psychology, 2018)
Introduction: Scuba diving is an important marine tourism sector, but requires proper safety standards to reduce the risks and increase accessibility to its market. To achieve safety goals, safety awareness and positive safety attitudes in recreational scuba diving operations are essential. However, there is no published research exclusively focusing on scuba divers’ and dive centres’ perceptions towards safety. This study assessed safety perceptions in recreational scuba diving operations, with the aim to inform and enhance safety and risk management programmes within the scuba diving tourism industry. Materials and Methods: Two structured questionnaire surveys were prepared by the organisation Divers Alert Network (DAN) and administered online to scuba diving operators in Italy and scuba divers in Europe, using a mixture of convenience and snowball sampling. Questions in the survey included experience and safety offered at the dive centre; the buddy system; equipment and accessories for safe diving activities; safety issues in the certification of new scuba divers; incidents/accidents; and attitudes towards safety. Results: 91 scuba diving centres and 3 766 scuba divers participated in the study. Scuba divers gave importance to safety and the responsiveness of service providers, here represented by the dive centres. However, they underestimated the importance of a personal emergency action/assistance plan and, partly, of the buddy system alongside other safety procedures. Scuba divers agreed that some risks, such as those associated with running out of gas, deserve attention. Dive centres gave importance to aspects such as training and emergency action/assistance plans. However, they were limitedly involved in safety campaigning. Dive centres’ perceptions of safety in part aligned with those of scuba divers, with some exceptions. Conclusion: Greater responsibility is required in raising awareness and educating scuba divers, through participation in prevention campaigns and training. The study supports the introduction of programmes aiming to create a culture of safety among dive centres and scuba divers. Two examples, which are described in this paper, include the Hazard Identification and Risk Assessment (HIRA) protocol for dive centres and scuba divers, and the Diving Safety Officer (DSO) programme to create awareness, improve risk management, and mitigate health and safety risks.